Individual knowledge of, perceptions about, and barriers to physical literacy (PL) in Malaysia - Zulkifli Ahmad Fahim; Danis Ajau (Sciendo, 2021)
The purpose of this study was to evaluate individuals' knowledge of, perceptions about, and barriers to promoting physical literacy (PL) in Malaysia. Random samples of 360 participants of different genders, ages, races, and education levels (aged 15-60 years) residing in Malaysia participated in this study, which was conducted on online platforms between the months of February and May, 2019. The participants' knowledge was assessed using a modified Physical Literacy Knowledge questionnaire (PLKQ). Open-ended questions were also conducted to assess perceived perceptions and barriers to improving participants' PL, thus strengthening the validity and reliability of data collection. Quantitative data were analyzed using descriptive statistics (e.g., means, SD) and the Pearson correlation coefficient, while the analysis of qualitative data involved the usage of the Interpretive Phenomenological Approach (IPA). The participants showed greater efficacy about standards in physical education and believed that PL is developed throughout one's lifetime, with (M = 3.2, SD = 1.02) and (M = 3.78, SD = 1.02), respectively. Additionally, most participants pointed to the necessity of having specific skills and experience to develop PL among young people as the main barrier to improving PL in Malaysia, with (M = 3.25, SD = 1.02). This initial study will provide better direction for future researchers and educators to plan an intervention to increase PL among Malaysians and advocate for physical activity in individuals' daily lives. Additionally, this study will be useful to inform future educators' teaching practices, particularly in Malaysian schools.